The Application of Alkali Activator and Admixture for High Early Concrete Compressive Strength with GGBFS Substitution - Elvina Juesmin; Iman Satyarno; Suprapto Siswosukarto; Ratna Dwiyani Nawangsasi; Muhammad Hasan Taufiq (Universitas Negeri Yogyakarta, 2025)
Concrete with high early compressive strength is designed to reach at least 20 MPa within the first 24 hours after casting. However, achieving this generally requires increased cement content, which unfortunately leads to higher carbon emissions and production costs. To reduce this impact, cement can be partially substituted with pozzolans such as ground granulated blast furnace slag (GGBFS), which has a chemical composition similar to cement. Nevertheless, GGBFS exhibits a slow hydration process; therefore, an alkali activator is required to accelerate the reaction. On the other hand, alkali activation can reduce concrete workability, making the addition of admixtures such as superplasticizers necessary to maintain adequate workability. This study investigates the effect of adding alkali activators and admixtures on concrete's early compressive strength and workability of concrete incorporating GGBFS as a cement substitute. Ordinary Portland cement and GGBFS were used at a ratio of 70:30. The alkali activator consisted of NaOH and Na₂SiO₃, with a Na₂SiO₃/NaOH ratio (R) of 1.5 and a total alkali-to-GGBFS ratio (A) of 0.45. The superplasticizer was Sika® ViscoCrete®-1050 HE at at dosages of 0.5% and 1%. The alkali activator contents tested were 0%, 2.5%, 5%, 7.5%, and 10%. The paste-to-fine aggregate void ratio (Rm) and the mortar-to-coarse aggregate void ratio (Rb) were both set at 1.4. Workability was evaluated using the slump test, while compressive strength was measured at 24 hours. The results showed that the addition of an alkali activator led to a substantial improvement in the compressive strength of the concrete, reaching up to 114.8% of the minimum required early compressive strength. The compressive strength peaked at 43 MPa when 10% alkali activator was added to the mixture. However, increasing the alkali activator content significantly reduced workability, with the slump value reaching zero at the 10% dosage. The addition of a superplasticizer was proven to be necessary to maintain a balance between early strength and concrete workability.